2004
DOI: 10.5694/j.1326-5377.2004.tb06233.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of health assessments for older Australian veterans and war widows

Abstract: Objective: To assess the effect of home‐based health assessments for older Australians on health‐related quality of life, hospital and nursing home admissions, and death. Design: Randomised controlled trial of the effect of health assessments over 3 years. Participants and setting: 1569 community‐living veterans and war widows receiving full benefits from the Department of Veterans’ Affairs and aged 70 years or over were randomly selected in 1997 from 10 regions of New South Wales and Queensland and randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 21 publications
2
63
0
8
Order By: Relevance
“…Participants lost to follow-up for other reasons more often had a non-Caucasian ethnic background, had a lower socioeconomic status, were more often disabled and were less able to participate. These findings are in accordance with the literature [8], [21][26], although some authors found no difference between responders and those lost to follow-up [28] or assumed nonselective loss to follow-up [9], [29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Participants lost to follow-up for other reasons more often had a non-Caucasian ethnic background, had a lower socioeconomic status, were more often disabled and were less able to participate. These findings are in accordance with the literature [8], [21][26], although some authors found no difference between responders and those lost to follow-up [28] or assumed nonselective loss to follow-up [9], [29].…”
Section: Discussionsupporting
confidence: 92%
“…Large national studies use surveys to routinely collect these self-reported data [4]–[9]. Self-report is mostly an effective and less time-consuming mode of collecting data on the utilization of healthcare resources compared to collecting data from medical records or administrative claims data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ameliorating this situation may require not only further promotion of the items with doctors but further engagement of local primary health infrastructure and the community. [2,5] The evaluation of the HA items and previous initiatives to promote health checks[11] in Aboriginal and Torres Strait islander communities are valuable resources in developing approaches to ensure that the potential health benefit deriving from the new and existing items are delivered.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] No information was available on baseline levels for the provision of HAs but the evaluation did suggest that there was an increase in the use of HAs in case study practices and that reimbursement was an incentive to completing HAs in about one third of practices. Health benefits associated with HA among older patients were relatively small [4,5] and the evaluation suggested that further uptake was required to have significant impact on the health of the target populations. [3] This was particularly true of the items for Aboriginal and Torres Strait Islander people which were used at a significantly lower rate than the items for the general population.…”
mentioning
confidence: 99%